DEVELOPMENT OF AN ALGORITHM FOR DETECTING DENTAL DISEASES AND PROVIDING DENTAL CARE TO CHEMICAL INDUSTRY WORKERS - Sunatullo A. Gafforov; Feruza I. Ibragimova (Central Asian Journal of Medicine, 2023)
The question of the negative impact of some industries on the oral cavity remains relevant. The relationship of the high prevalence of non-carious lesions of the teeth and oral mucosa with such industrial processes as oil and gas extraction, metallurgy, chemical production, bakery and confectionery production has been proven. Dental health contributes to the preservation of the ability to work of an important part of the non–population of the country - workers of industrial enterprises, especially since a number of studies convincingly reveal the role of the dental system in the general state of the body. [2,6,8,] The presence of high risks of occupational diseases among workers in industry has been proven. This is due to the entry of compounds of elements into the human body through the oral cavity. Industrial workers are characterized by a high prevalence of dental caries and inflammatory periodontal diseases.